The Future of Intelligent Networks in Developing Countries - Rwangoga, Narcis T.; Ngobye, Martin (My University, 2022)
Telecommunication networks have become important not only for the academic community but also for users in business and industry. As globalization takes shape, this trend applies to both developed and developing countries. Unfortunately for many developing countries, the telecommunication networks are still dominated by the public switched telephone networks (PSTN), which are not able to support rising demand for services through networked systems. Innovative solutions have to be devised to plan, design and implement telecommunication networks that are able to seamlessly provide services demanded through the network today. This applies to both wired and wireless networks. The demand for network based services has risen in developing countries, considering how wireless technologies for cellular and personal communications have been extended to most areas in developing countries. Intelligent Networks (IN) is a promise that countries which are implementing telecommunication networks can use to deliver network based services. In this paper, we explore and discuss why IN provides the promise and requirements for their implementation. The objective is to provide a basis a tool for telecommunication network planers and implementers can use for IN structure implementation in developing countries where resources are highly constrained